2020
DOI: 10.3390/jcm9040910
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Decreases the Level of PCSK9—A Novel Indicator of the Risk of Proatherogenic Lipid Profile in Psoriasis. The Preliminary Data

Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) exerts an important role in inflammatory processes, lipids homeostasis, and cardiometabolic disorders that are closely associated with psoriasis. The aim of the study was to analyze the clinical and diagnostic value of serum PCSK9 concentrations and their connections with disease severity, inflammation, metabolic syndrome, and impact of systemic therapies in psoriatic patients. The study enrolled thirty-five patients with active plaque-type psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Psoriasis is a systemic disease closely related with CMDs mainly through metabolically-driven inflammation. Recent papers published by our team and others showed that psoriatics still require discoveries of new markers of the disease as well as underlying conditions related to the psoriatic progression [1,20]. KLFs have been an area of intense research lately and thus they constitute a huge excitement for their potential role in medicine, in multiple diseases, not only CVD, but also psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a systemic disease closely related with CMDs mainly through metabolically-driven inflammation. Recent papers published by our team and others showed that psoriatics still require discoveries of new markers of the disease as well as underlying conditions related to the psoriatic progression [1,20]. KLFs have been an area of intense research lately and thus they constitute a huge excitement for their potential role in medicine, in multiple diseases, not only CVD, but also psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 inhibitors act by inhibiting PCSK9 (proprotein convertase subtilisin/kexin type 9), which prevents the binding of PCSK9 with LDL receptors on hepatocytes and the loss of such receptors, resulting in upregulation of their number and a decrease in LDL blood concentration [ 58 ]. Our team of dermatologists has investigated PCSK9 serum concentration in psoriatic patients and discovered that PCSK9 levels are significantly elevated in such patients and may become a marker of cardiometabolic disorder risk in PSO [ 62 ].…”
Section: The Influence Of Lipid-lowering Drugs On Psoriasismentioning
confidence: 99%
“…Secondly, our RA patients were in remission or low disease activity; hence we could not evaluate an association between inflammation in RA, subclinical CVD and PCSK9 levels. Lastly, specific RA-related therapies were not included in the analysis, due to the small sample size, even if there are indications from recent publications that they could affect PCSK9 levels or even lipid profile in RA (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%